"The Vietnamese have a better understanding of yidishkeit than the Jewish Federation officials": A senior day center in historical perspective. Issue 2 (3rd July 2017) - Peltz, Rakhmiel
ABSTRACT: In 2011, a Jewish-sponsored senior center that had served older Jews and non-Jews for decades was forced to close. This article describes the meaning of the senior center to its participants and the impact of its closing on its members. The closing of the center raises larger questions about the potential role of older adults in the life of the larger community and how the loss of such institutions can inhibit the ability of older adults to contribute to and enrich the lives of all members of their communities.